Bearing Capacity Parameters for Pipe Piles in Stiff to Hard Highly Plastic Clays (Journal of Building and Road Research, 2021)
The design of steel pipe piles in clay soils is faced with insufficient information regarding the parameters used forestimation of their static ultimate load capacity, namely the adhesion factor and plug length.This paper gives guides forthe selection of the mentioned parameters. Direct shear and adhesion tests were performed. The soil tested is highly plasticsilty clay statically compacted in the shear box at constant dry density and varying water content covering dry and wet ofoptimum water content. The adhesion factorwas computed for each test condition. An average value of 0.48 was foundfor the interface resistance when the water content is lower than the plastic limit. The factor was found to increase withincrease in water content for water content higher than the plastic limit.The Plug length data was generated from a construction site in Melut Basin in Southern Sudanwhere steel pipe piles of differentsizes were driven in very stiff to hard silty clay to about the same length and driving records were recorded with extra dataregarding plug lengths. Geotechnical investigation preceded the construction activities. The plug data was analyzed for theeffects of pile diameter and soil conditions on the plug length. Plug length to diameter ratio ranged between 3.8 and 8.0. Pluglength increased linearly with increasing pile diameter and an excellent linear relationship was obtained between the averageplug length for each diameter and pile diameter. Piles with small diameter gave lower resistance to penetration compared withthose with larger diameters.